The effect of addition EVA and LDPE-g-MAH on irradiated LDPE filled with metal hydroxides - Sabet, Maziyar (Taylor and Francis Inc., 2014)
Electron beam irradiation efffects on polymer cross-linking used for wire and cable insulations are still being researched. This study showed that upon irradiation, ethylene vinyl acetate (EVA) and maleic anhydride grafted polyethylene (LDPE-g-MAH) addition as coupling agent to the LDPE/fillers, improved processing and mechanical properties of compounds at each irradiation dosage (0110 kGy). A gradual increase in gel content (GC) and tensile strength (TS) with a concomitant decline in elongation at break (EB), hot set (HS) and densities of compounds were observed upon irradiation of the blends. Melt flow index test (MFI) results revealed that filler addition reduced compounds flowing and in consequence, caused difficult to process. The LDPE/EVA blends TS values decreased significantly with fillers addition (ATH, MH and ZB). Consequently, this study demonstrated that filler addition to irradiated low density polyethylene (LDPE) impaired processing and mechanical properties of compounds, whereas, LDPE-g-MAH (6-12 phr) and EVA (0-100 phr) addition to the compounds (1I-8I) improved the blends flowability and mechanical properties at each irradiation dose (0-110 kGy). Moreover, among additive fillers, MH content compounds presented the strongest adhesion forces with polymeric compounds compared with analog compounds content aluminum trihydrate (ATH) or zinc borate (ZB) at each irradiation dosage.